The culture map : breaking through the invisible boundaries of global business - Meyer, Erin. (U.S.A. : PublicAffairs, Perseus Books Group, 2014)
"As today's business world becomes ever-more global and virtual, executives and managers are expected to work harmoniously together with counterparts from a broad array dramatically different cultures and backgrounds, often without leaving their desks. But when you throw people together who come from starkly different backgrounds and cultures- from Americans who precede anything negative with three nice comments to French, Dutch, Israelis and Germans who get straight to the point ("your presentation was simply awful"); from Latin Americans and Asians who are steeped in hierarchy to the Scandinavians who think the best boss is just one of the crowd- the result can sometimes be disastrous. Even with English as a global language, it's easy to fall into cultural traps that endanger careers and sink deals. In The Culture Map, renowned expert Erin Meyer offers highly practical and timely perspective on one of today's most pressing business issues: how do different cultures influence the way to do business when working globally? And she explains how to dramatically increase business success by improving one's ability to understand the cultural drivers of colleagues, clients, and suppliers from different countries. With the rapid increase in global call centers, outsourcing, supply chains, and project teams, cultural diversity touches almost everyone. Globalization has led to the rapid connection of internationally based employees from all levels of multinational companies. The advent of information and communication technology means that work itself has globalized. Where once you might have been expected to collaborate with colleagues from one or two foreign territories, today many people are part of global networks connected with people scattered around the world. Yet most managers have little understanding of how local culture impacts global interaction. Even those who are culturally informed, travel extensively, and have lived abroad often have few strategies for dealing with the cross-cultural complexity that affects their team's day-to-day effectiveness. The Culture Map provides a new way forward, with vital insights for working effectively and sensitively with one's counterparts in the new global marketplace"--
"As today's business world becomes ever-more global and virtual, executives and managers are expected to work harmoniously together with counterparts from a broad array of dramatically different cultures and backgrounds, often without leaving their desks. But when you throw people together who come from starkly different backgrounds and cultures-- from Americans who precede anything negative with three nice comments to French, Dutch, Israelis and Germans who get straight to the point ("your presentation was simply awful"); from Latin Americans and Asians who are steeped in hierarchy to the Scandinavians who think the best boss is just one of the crowd-- the result can sometimes be disastrous. In Culture Map, renowned expert Erin Meyer offers highly practical and timely perspective on one of today's most pressing business issues: how do different cultures influence the way to do business when working globally? And she explains how to dramatically increase business success by improving one's ability to understand the cultural drivers of colleagues, clients, and suppliers from different countries. Culture Map provides a new way forward, with vital insights for working effectively and sensitively with one's counterparts in the new global marketplace"--
Includes bibliographical references and index.
Keywords: Diversity in the workplace; Psychology, Industrial; Interpersonal relations; BUSINESS & ECONOMICS / Workplace Culture; PSYCHOLOGY / Interpersonal Relations; PSYCHOLOGY / Industrial & Organizational Psychology; LANGUAGE ARTS & DISCIPLINES / Communication Studies